2021
DOI: 10.1039/d0cp06081j
|View full text |Cite
|
Sign up to set email alerts
|

Photoelectron spectroscopy and theoretical study of AlnC5−/0 (n = 1–5) clusters: structural evolution, relative stability of star-like clusters, and planar tetracoordinate carbon structures

Abstract: The structures of AlC5−/0 and Al2C5−/0 are linear while those of Al3C5−/0, Al4C5−/0, and Al5C5−/0 are two-dimensional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 71 publications
1
15
0
Order By: Relevance
“…Here, our prime focus is on two molecules, (SP-4)-spiro[2.2]pent-1,4-dien-1,4-diyl ( 11 ) and (SP-4)-spiro[2.2]pent-1,4-dien-1,5-diyl ( 13 ), that contain a planar tetracoordinate carbon (ptC) atom. 23 − 26 Though molecules with a ptC atom deviate from the traditional aspects of the tetrahedral tetracoordinate nature of carbon, which is one of the cornerstones of organic chemistry, tremendous interest has been paid by both experimentalists 27 31 and theoreticians 32 − 42 in this new class of molecules as they could potentially be used as new materials. With respect to C 5 H 2 , the relevance of isomers 11 and 13 in the formation of 2 is theoretically established here.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, our prime focus is on two molecules, (SP-4)-spiro[2.2]pent-1,4-dien-1,4-diyl ( 11 ) and (SP-4)-spiro[2.2]pent-1,4-dien-1,5-diyl ( 13 ), that contain a planar tetracoordinate carbon (ptC) atom. 23 − 26 Though molecules with a ptC atom deviate from the traditional aspects of the tetrahedral tetracoordinate nature of carbon, which is one of the cornerstones of organic chemistry, tremendous interest has been paid by both experimentalists 27 31 and theoreticians 32 − 42 in this new class of molecules as they could potentially be used as new materials. With respect to C 5 H 2 , the relevance of isomers 11 and 13 in the formation of 2 is theoretically established here.…”
Section: Introductionmentioning
confidence: 99%
“…Despite all these experimental evidence, our recent theoretical studies have predicted that three singlet polar carbenes, bent-pentadiynylidene ( 4 ), buta-1,3-diynylcarbene ( 6 ), and 2-methylenebicyclo[1.1.0]­but-1(3)-en-4-ylidene ( 9 ), are yet to be identified in the laboratory. , Thus, further theoretical exploration of C 5 H 2 isomers became a natural prerequisite. Here, our prime focus is on two molecules, (SP-4)-spiro[2.2]­pent-1,4-dien-1,4-diyl ( 11 ) and (SP-4)-spiro[2.2]­pent-1,4-dien-1,5-diyl ( 13 ), that contain a planar tetracoordinate carbon (ptC) atom. Though molecules with a ptC atom deviate from the traditional aspects of the tetrahedral tetracoordinate nature of carbon, which is one of the cornerstones of organic chemistry, tremendous interest has been paid by both experimentalists and theoreticians in this new class of molecules as they could potentially be used as new materials. With respect to C 5 H 2 , the relevance of isomers 11 and 13 in the formation of 2 is theoretically established here.…”
Section: Introductionmentioning
confidence: 99%
“…[20] The structure and bonding of linear Al2C2 0,were computationally and experimentally investigated by Cannon and Li et.al. [21] Recently, the structures of linear AlC5and Al2C5have been confirmed using anion photoelectron spectroscopy by Zhang et al [22].…”
Section: Introductionmentioning
confidence: 94%
“…Recently spectroscopic characterization of Alcontaining clusters have gained considerable interest. [22] Therefore, the relevant spectroscopic parameters, such as ionization energy, electron affinity, vertical detachment energy of the molecules, were calculated, and the variation was explained with an increasing number of carbon and Al atoms. The ionization energy and electron affinity are essential parameters to characterize the structures and to study the reactivity of the molecules under various experimental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…5 At the same time, Rao et al also experimentally observed the planar tetracoordinate nitrogen (ptN) NAl 4 − predicted by Schleyer and Boldyrev in 1991. 6 Remarkably, the star-like ptC cluster C 5 Al 5 − predicted by Wu's group in 2011 was recently realized experimentally by Zhang et al 7 The PES experimental technique, however, also has significant limitations, and generally only mono-anionic species with simple components (as mentioned earlier) are detected by it among a large number of predicted planar clusters. In particular, more than half of the theoretical predictions for planar pentacoordinate carbons are beryllium related, 1,8 but these clusters have not been hitherto detected experimentally.…”
mentioning
confidence: 92%